Red and blue channels correction based on green channel and median-based dual-intensity images fusion for turbid underwater image quality enhancement - Kamil Zakwan, Mohd Azmi; Ahmad Shahrizan, Abdul Ghani; Zulkifli, Md. Yusof (Springer, 2020)
One of the main problems encountered in processing the turbid underwater images is the effect of greenish color cast that overshadows the actual color of an object. This paper introduces a new technique which focuses on the enhancement of turbid underwater images. The proposed method integrates two major steps. The first step is specially designed to reduce the greenish color cast problem. The blue and red channels are improved according to the difference between these channels and the reference channel in terms of the total pixel values. Then, the median-based dual-intensity images fusion approach is applied to all color channels to improve the image contrast. Qualitative and quantitative evaluation is used to test the effectiveness of the proposed method. The results show that the proposed method is very effective in improving the visibility of the turbid underwater images.